The Sugar‐To‐Flower Shallow Cumulus Transition Under the Influences of Diel Cycle and Free‐Tropospheric Mineral Dust - Pornampai Narenpitak; Jan Kazil; Takanobu Yamaguchi; Patricia K. Quinn; Graham Feingold (Journal of Advances in Modeling Earth Systems, 2023)
Abstract A shallow cumulus cloud transition from a sugar to flower type of organization occurred under a layer of mineral dust on 2 February 2020, during the multinational Atlantic Tradewind Ocean‐Atmosphere Mesoscale Interaction Campaign (ATOMIC) and the Elucidating the Role of Clouds‐Circulation Coupling in Climate (EUREC4A) campaigns. Lagrangian large eddy simulations following an airmass trajectory along the tradewinds are used to explore radiative impacts of the diel cycle and mineral dust on the sugar‐to‐flower (S2F) cloud transition. The large‐scale meteorological forcing is derived from the European Center for Medium‐Range Weather Forecasts Reanalysis Fifth Generation and based on aerosol measurements from the U.S. Ronald H. Brown Research Vessel and the French ATR‐42 Research Aircraft during the field campaigns. A 12‐hr delay in the diel cycle accelerates the S2F transition at night, leading to more cloud liquid water and precipitation. The aggregated clouds generate more and stronger cold pools, which alter the original mechanism responsible for the organization. Although there is still mesoscale moisture convergence in the cloud layer, the near‐surface divergence associated with cold pools transports the subcloud moisture to the drier surrounding regions. New convection forms along the cold‐pool edges, generating new flower clouds. The modulation of the surface radiative budget by free‐tropospheric mineral dust poses a less dramatic effect on the S2F transition. Mineral dust releases longwave radiation, reducing the cloud amount at night, and absorbs shortwave radiation during the day, cooling the boundary‐layer temperature and increasing the overall cloud amount. Cloud‐top radiative heating because of more clouds strengthens the mesoscale organization, enlarging the aggregate areas, and increasing the cloud amount further.